Nanostructured Materials for Solar Energy Conversion 2006
DOI: 10.1016/b978-044452844-5/50013-5
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Photosynthetic Materials and Architectures to Solar Cells

Abstract: Photosynthetic approaches to redesigning photovoltaics (PV) oer an attractive route towards achieving high-eciency, low-cost solar energy transduction. This thesis explores two routes toward this end: the direct integration of photosynthetic structures into solid-state devices and the architectural redesign of organic solar cells to more closely parallel photosynthesis.The highly ecient photosynthetic reaction center is the site of exciton dissociation in photosynthesis, analogous to the role of the donor-acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…In a previous work [35], researchers have reported loss of spectroscopic properties when Chl-a molecules deposited as thin films were exposed directly to oxygen. As such, we have shown that by impregnating Chl-a molecules into CMC matrix forming thin films, an encapsulating effect is achieved which prolongs the optical functionality of the photosynthetic pigment.…”
Section: Optimum Cmc Concentration Effectmentioning
confidence: 99%
“…In a previous work [35], researchers have reported loss of spectroscopic properties when Chl-a molecules deposited as thin films were exposed directly to oxygen. As such, we have shown that by impregnating Chl-a molecules into CMC matrix forming thin films, an encapsulating effect is achieved which prolongs the optical functionality of the photosynthetic pigment.…”
Section: Optimum Cmc Concentration Effectmentioning
confidence: 99%